What explains public transport use? Evidence from seven European cities - Gascon, M; Marquet, O; Gràcia-Lavedan, E; Ambròs, A; Götschi, T; Nazelle, ADE; Panis, LI; Gerike, R; Brand, C; Dons, E; Eriksson, U; Iacorossi, F; et al. (Elsevier, 2020)
Background the relationships between the built environment characteristics and personal factors influencing public transport use and the ways they interact are not well understood.